C‐Silyl‐N, N‐dialkyl‐N′‐arylformamidines: Synthesis and Reactions with Phosphorus(III) Chlorides. Issue 29 (20th September 2016) - Marchenko, Anatoliy; Koidan, Georgyi; Hurieva, Anastasiya; Vlasenko, Yurii; Kostyuk, Aleksandr
Abstract : A method for the synthesis of new C ‐silyl‐ N, N ‐dialkyl‐ N′ ‐arylformamidines was developed. These derivatives were formed by the deprotonation of N ‐(trimethylsilyl)formamidinium salts to give the corresponding N ‐trimethylsilyl carbenes followed by a 1, 2‐migration of the silyl group. The reactions of C ‐silylformamidines with phosphorus(III) chlorides were then studied. The reactions between chlorodiphenylphosphane and the C ‐silylformamidines readily afforded C ‐phosphanylformamidines in high yields. The reactions of dichlorophosphanes and C ‐silylformamidines yielded previously unknown phosphanes that feature two formamidine substituents. In the reaction with phosphorus trichloride, the sterically least encumbered formamidine gave a stable two‐coordinate compound through the formation of an intermediate tris(phosphane). The reactions of the sterically more encumbered formamidines led to the substitution of only two chlorine atoms to give a chlorophosphane or benzazaphosphole. The structures of key compounds were proven by X‐ray crystal structure analyses. Abstract : A convenient preparative method for the synthesis of C ‐silyl‐ N, N ‐dialkyl‐ N′ ‐arylformamidines was developed. These derivatives were employed as nucleophiles in reactions with phosphorus(III) chlorides to afford phosphanes that feature one or two formamidine substituents. We were unable to introduce three formamidine substituents into the final product.